HUBUNGAN KONSEP DIRI SISWA DENGAN TINGKAH LAKU SOSIAL SISWA - Annisa Apriliyanti; Mudjiran Mudjiran; Mursyid Ridha (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
In General, students who are likely to have a positive self concept will behave so socially positive, otherwise. This study aims to look at the description of the concept of self and social behaviour of students as well as revealing how the relationship between the concept of yourself with social behaviour SMK Negeri 6 students in the field. This research is descriptive research korelasional that saw the relationship between the concept of yourself with social behaviour SMK Negeri 6 students in the field. This research sample 84 students. This research instruments such as questionnaires. Findings revealed: there is a significant relationship between self concept with social behaviour with categories being.